A new approach based on modal mass distribution matrix to identify weak components of machine tool structure. Issue 1 (March 2016) - He, Songping; Mao, Xinyong; Liu, Xiangqiu; Luo, Bo; Li, Bin; Peng, Fangyu
Abstract The dynamics of the machine tool structure are significant in high-precision machining and are meaningful to be evaluated. This paper proposes a new approach based on the modal mass distribution matrix to evaluate the dynamics and identify the weak components of machine tool structure and then to investigate the various components' effects on the machining process in different frequency bands. First, the approach is developed and verified by a designed mass-spring model whose weak components are known. Then, the proposed approach is used to identify the weak components of a machine tool structure whose modal parameters are obtained by experimental modal analysis. The result shows that the same component presents different weakness levels at different modes and that the various components of the structure present different weakness levels at the same mode. Finally, a cutting experiment is then conducted to verify the identification result. The result meets the former weak components' identification result well.